Korean religions in relation: Buddhism, Confucianism, Christianity - Min, Anselm Kyongsuk; Kang, Wi Jo (SUNY series in Korean studies, 2016)
Buddhism and Confucianism: Accommodation and Conflict -- Confucianism and Catholicism: Conflict and Assimilation -- Protestantism and Korean Religions: Exclusion and Assimilation -- Confucianism, Christianity, and the Challenges of the Modern World